Dryad_mtDNA_Sebastes_Peter_Shum_Genbank_KP988027–KP988288 - Shum, Peter; Pampoulie, Christophe; Kristinsson, Kristján; Mariani, Stefano (Dryad Digital Repository, 2015)
Mitochondrial control region of North Atlantic Sebastes (S. viviparus, S. fasciatus, S. norvegicus, S. mentella)